Influence of thermal treatment on microstructure, mechanical and degradation properties of Zn-3Mg alloy as potential biodegradable implant material - Dambatta, M. S. (Elsevier, 2015)
In this study, the influence of homogenisation heat treatment effect on Zn-3Mg alloy proposed for biodegradable bone implants was investigated. The alloy was developed via casting process from high purity raw materials and homogenised at 360°C for 15h followed by water quenching. Results revealed that the microstructure of as cast alloy was composed of dendritic structure of Zn-rich phase distributed in segregated pattern within Mg2Zn11 eutectic phase. Exposure to the long duration heating of homogenisation apparently broke the dendrites and transformed them into connected precipitates within the alloy's matrix. Non-equilibrium thermal analysis revealed the formation of Mg2Zn11 eutectic phase which nucleated at 367°C and solidified completely at 354°C. The eutectic coherency point occurred at 368°C and 424s when 30% of solid has precipitated during solidification. Homogenisation resulted into lowering the alloy's tensile strength from 104MPa to 88MPa but improving elongation at fracture from 2.3% to 8.8%. The homogenised Zn-3Mg alloy showed improved corrosion resistance (corrosion rate=0.13mmpy) compared to the as-cast one (corrosion rate=0.21mmpy). The mechanical property and corrosion behaviour of the homogenised alloy seem suitable for biodegradable implant applications